Profiling selectivity of chagasin mutants towards cysteine proteases cruzain or cathepsin L through molecular dynamics simulations. Issue 16 (2nd November 2021) - Toman, Núbia Prates; Kamenik, Anna Sophia; Santos, Lucianna Helene; Hofer, Florian; Liedl, Klaus R.; Ferreira, Rafaela Salgado
Abstract: Chagasin, an endogenous cysteine protease inhibitor from Trypanosoma cruzi, can control the activity of the parasitic cruzain and its homologous human cathepsin L. While chagasin inhibits both enzymes with similar potency, mutations have different effects on binding to these enzymes. Mutants T31A and T31A/T32A bind well to cathepsin L, but their affinity for cruzain drops ∼40 to 140–fold. On the other hand, the mutant W93A binds well to cruzain, but it loses potency against cathepsin L. Here, we employed molecular dynamics simulations to understand the selectivity in inhibition of cruzain or cathepsin L by chagasin mutants W93A, T31A, and T31A/T32A. Our results allowed profiling the nonbonded interactions in the interfaces of each mutant with these cysteine proteases. Additionally, we observed differences in the binding conformation of the chagasin loops L2 and L6 of the W93A mutant, favoring interactions with cruzain and reducing interactions with cathepsin L. These differences are associated with a partial dissociation of the W93A-cathepsin L complex, providing a likely cause for the selectivity of the mutant W93A towards cruzain. Communicated by Ramaswamy H. Sarma.